MODAL SOSIAL MASYARAKAT DALAM PEMENUHAN KEBUTUHAN RUMAH LAYAK HUNI (Studi Kasus Program Peremajaan Perumahan di Kawasan-kawasan Kumuh melalui Pengembangan Perumahan secara Vertikal di Kelurahan Kaligawe, Kecamatan Gayamsari, Kota Semarang) - Aprilia, Yovita Annisa; Suryaningsih, Margaretha; Djumiarti, Titik (Journal of Public Policy and Management Review, 2015)
Social capital closely relates with society and so do it. Its scope is broad and it is flexible cause social capital can enter various aspects in the life of. Concepts about social capital consisting of elements that there are in it such as social participation, social network, social institution, a norm and social value. Research methodology descriptive with a qualitative approach used in this research to identify factors that influence in the formation of social capital at Rusunawa Kaligawe. The result of the research showed factors that influence in the formation of social capital related to the habit of, the status and the role of individual at Rusunawa Kaligawe, education, the social class and economic gap, and the consumption patterns of individual and values personal. The habits of inhabitant’s Rusunawa Kaligawe are throwing trash in any place and delaying the payment of the rent. The inhabitant who as a head of RT or RW so it would affect to their environment intercommunication, prestige and their rights and duties. Education is done by the inhabitant of the Rusunawa Kaligawe are formal and non formal education. The social class and economic gap able to be seen through by education and the income derived the inhabitant of the Rusunawa Kaligawe. In the consumption, the inhabitant of the Rusunawa Kaligawe often put the payment of the rent in the end of expenditure needs of their list. Based on that result, this research recommends the head of RT or RW to apply system fines for inhabitant who littering. Making all the things required are ready to the officers and proactive attitude an inhibitant in the payment of the rent. The socialization regarding Semarang mayor regulation number 7/2009 occupancy and tenancy toward rental house owned by Semarang government to the inhibitant. Wisdom the inhabitant of the Rusunawa Kaligawe in putting expenses as priority is important to the continuity of the payment of rent.